Actividades Físicas como alternativa para disminuir el sedentarismo en personas alcohólicas del Centro CETAD ‘‘NUEVO RENACER’’ de la ciudad de Loja, periodo 2024. - Azuero Perez, Daniel Alexander (2024)
The present Curriculum Integration Study was developed with the objective of evaluating how physical activity helps to reduce sedentary behavior in alcoholics of the CETAD “’NUEVO RENACER” Center in Loja city, period 2024. It was a mixed study, of a descriptive and correlational type and quasi-experimental design. Diagnostic instruments such as a survey, an observation sheet and a test were applied to a sample of 12 patients. According to the results obtained after applying the diagnostic instruments, it is evident that 58.31% of the investigated population prefer aerobic and anaerobic exercises as activities to be performed. Regarding to their interest in performing physical activity, 100% of the population is interested and 100% of the population considers that performing physical activities helps their physical and mental well-being. Based on these results, a plan of physical activities was designed and applied as an alternative to decrease sedentary behavior. This plan was structured in 17 sessions of physical activities focused on aerobic and anaerobic exercises. Then, control instruments were applied in which there was evidence of an improvement in their physical and mental health. It is concluded that before the implementation of the physical activity plan there were certain difficulties such as fast fatigue, lack of mobility and health problems of patients; however, the application of a final test in the plan showed improvements in the aforementioned aspects, demonstrating thus the effectiveness of physical activities as an alternative to reduce sedentary behavior in alcoholic patients. Keywords: Physical activity, Alcoholism, Sedentary lifestyle, Methodology.